The Impact of Covid-19 Pandemic on Micro, Small and Medium Enterprises in Kotabaru Regency, Indonesia - Dayat Ikhsan Hajati (Journal of Research in Business, Economics, and Education, 2021)
This study aims to find out the impact of the COVID-19 pandemic on MSME turnover, profit, capital, product distribution and raw materials in Kotabaru Regency. This study carried out using a quantitative method with the type of case study with the population of MSMEs in Kotabaru. The sampling technique in this study used simple random sampling with a total sample of 385 MSMEs obtained based on Lameshow’s formula. The collecting data in this study used observation, literature study and questionnaires. The data analysis technique used descriptive statistical analysis and inferential statistical analysis with the Wilcoxon Signed Rank Test. The results of the study showed that 1) there were significant difference in turnover and profit got by MSMEs in the form of an average decrease in turnover and profit between before and during the COVID-19 Pandemic in Kotabaru Regency, 2) MSMEs were quite experiencing difficulties in capital turnover, supply chain of raw materials and distribution of during the COVID-19 Pandemic in Kotabaru Regency.